Introgression of bruchid (Zabrotes subfasciatus) resistance into small red common bean (Phaseolus vulgaris) background and validation of the BRU_00261 (snpPV0007) resistance marker. (9th October 2021) - Tigist, Shiferaw Girsil; Raatz, Bodo; Assefa, Amelework; Melis, Rob; Sibiya, Julia; Keneni, Gemechu; Mukankusi, Clare; Fenta, Berhanu; Ketema, Selamawit; Tsegaye, Dagmawit
Abstract: Bruchids are a major storage pest of common bean. Genetic resistance is a suitable method to avoid grain losses during storage. The objective of the study was to introgress the arcelin‐based resistance locus into selected advanced breeding line and to validate the molecular marker BRU_00261. A total of 208 progeny F4 families were phenotyped using a randomized complete block design, with three replications. Highly significant differences ( P < .001) among the entries, parents and offspring were recorded for almost all traits. There was no significant difference between the two parents in the number of eggs laid. The progenies were grouped as highly resistant (34.3%), resistant (11.9%), moderately resistant (21.4%) and susceptible (32.4%). The levels of broad sense heritability ranged from 68.5%–93.9% for all the traits. Eighty‐three most resistant lines and the parental lines were genotyped with the marker BRU_00261 (snpPV0007). The marker segregation deviated significantly from the expected independent segregation towards a strong enrichment for the resistant marker in the selected families. This marker will be useful for selecting promising materials in early generations and phenotypic confirmation of positive lines in later generations.